Volunteerism after the tsunami: Democratization and aid - Tiago Freire; Vernon Henderson; Ari Kuncoro (Brown University, Department of Economics, 2011)
Using three waves of survey data from fishing villages in Aceh, Indonesia for 2005-2009, we examine the determinants of local volunteer labor after the tsunami. Pre-existing social capital and the form of aid delivery (but not trauma) strongly affect village volunteerism initially, but these effects weaken with time. What persists is the effect of essentially a new institution, formal village elections. While recent work suggests democratization increases cooperation, the differentially timed introduction of elections negatively affects volunteerism, suggesting a regime switch effect where traditional leaders chosen by elites want more volunteer labor projects than democratically elected leaders do.
Keywords: 330; Überschwemmung; Katastrophenhilfe; Ehrenamtliche Arbeit; Social Capital; Lokales öffentliches Gut; Demokratisierung; Indonesien